Afluencia de visitantes y los atractivos turísticos de la Parroquia Febres Cordero del cantón Babahoyo - Peñafiel Leiton, Jorge Gustavo (2019)
The city of Babahoyo, land of great stories that promise a versatile city the same one that is growing in agro-turistically turning agricultural and livestock activities as its main source of income. This city is full culture in all its parishes, especially in that of Febres Cordero. Febres Cordero is a rural parish of the Babahoyo canton of the fovince of Los Ríos in Ecuador. Created in the precinct of Las Juntas on may 14, 1936. Its inhabitants are dedicated to agricultura, livestock and tourism. It is one of the most important sectores for agricultura that is primarilly engaged in the production of products such as: cocoa, rice, corn, plantain etc. Its parish head is the town of Mata de Cacao. Tourismo is one of the most booming activities in recent years, even in certain countries has been considered as one of the main source of considered as as one of the main sources of income, that is why some cities in the country work primarily to promote tourism because it is an activity that Great opportunities for growth an urban-rural development emerge for the future. For these characteristics, Babahoyo can not be the exception, tourism and agrotourism in its parishes have to be encouraged.